Effect of an educational program on adolescent premenstrual syndrome: lessons from the Great East Japan Earthquake - Takeda T; Shiina M (Dove Medical Press, 2018)
Takashi Takeda,1,2 Masami Shiina1 1Division of Women’s Health, Research Institute of Traditional Asian Medicine, Kindai University, Osaka, Japan; 2Department of Obstetrics and Gynecology, Tohoku University Graduate School of Medicine, Sendai, Japan Background: Catastrophic disasters such as great earthquakes cause tremendous physical and mental damage. We previously reported that the Great East Japan Earthquake worsened premenstrual symptoms among adolescent girls in the disaster-stricken area. Objectives: We reanalyzed these data to determine the positive effects of education on premenstrual symptoms. Materials and methods: Annual school-based surveys about premenstrual syndrome (PMS) or premenstrual dysphoric disorder (PMDD) have been conducted in Sendai since 2009. The Great East Japan Earthquake occurred on March 11, 2011. First-year students in one school had received education on PMS/PMDD before the earthquake, whereas those in another school had not. We reanalyzed data for 1431 girls (November 2010) and 1489 girls (December 2011) aged 15–18 years. Results: The severity of PMS/PMDD in students who had received the education program showed no changes between before and after the earthquake. However, students who had not received education showed worsening of the severity of PMS/PMDD. Conclusion: This study showed education had a possible beneficial effect for the prevention of stress-induced PMS/PMDD. Keywords: premenstrual syndrome, premenstrual dysphoric disorder, Great East Japan Earthquake, adolescents, education